Hantu Permintaan Radikal: Subjek Etis dalam Bayang-bayang Impotensi Refleksif - Laurensius Bagus Winardi (Retorik: Jurnal Ilmu Humaniora, 2022)
The gloomy political experiences, require ethics to get through of it. Simon Critchley argues that ethics is able to trigger the subject’s moral dimension to respond or reject the political system that pushes them into a state of depoliticization. Critchley's ethical theory is related to the formation of subjectivity, which includes the process of binding the self with concepts that are considered as good. Moral action or commitment depends on self-interaction with ideas of goodness received in the subject's ethical experience. Ethical experience is the space where motivation arises, where the self has agreed to be bound by the concepts of goodness, as an important arena for ethical subjectivity. Critchley's ethical experience and subjectivity are important concepts for his theory of the political subject. A subject that capable of demanding change when gloomy political experiences have become a common problem. Reflecting on Critchley's theory, this article attempts to map out the challenges to the ethical subject posited. Departing from Mark Fisher's exploration of reflexive impotence, this article then turns to how the subjectivity of the young generation in Indonesia has been regulated or imposed by institutions within the existing power structure. The state's need for ideal young citizens plays a role in the rejection of any ethical experience, thus hindering the process of ethical subjectivity.